PENGARUH PERAWATAN ORTHODONTIK CEKAT TERHADAP AKUMULASI PLAK DAN INFLAMASI GINGIVA PADA GIGI ANTERIOR RAHANG BAWAH ANAK - , Intan Chendana; , Drg. Sri Kuswandari, M.S., Sp. KGA(K), Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of fixed orthodontic appliance led to an increased of plaque accumulation and number of normal flora, especially around the gingival sulcus. On the other hand, the force that was imposed on the teeth can change the periodontal tissues especially gingival. The purpose of this study was to determine the effect of using fixed orthodontic appliance on plaque accumulation and gingival inflammation in the lower anterior teeth in 11-14 year olds children. Quasi-experimental study with pre-post test control group design was performed in 11 children aged 11-14 years. Observations of plaque accumulation was assessed by Orthodontic Plaque Index (OPI), while observations of gingival inflammation was assessed by the gingival index (GI) and the volume of Gingival sulcus fluid (GSF) (intrasulcular method) was done before the installation of fixed orthodontic appliance, on day-14, day-28, and day-42 after the installation of fixed orthodontic appliance. Data were analyzed by one-way Repeated ANOVA and then followed by Post Hoc LSD with paired t-test. Pearson Product Moment Correlation test for parametric data and Spearman for non-parametric data, followed by Linear Regression analysis with 95% confidence level. The study results showed a significant increase of OPI between all observation time, especially on day 14. There was a significant increase of CSG volume between observation time mainly between day 28 and day 42. The GI improvement is constant between observation time. There is a significant relationship between the OPI with GSF volume before fixed orthodontic treatment and day-42. Between OPI and GI, there was a significant relationship was found on days 28 and 42. The magnitude of the relationship between the OPI with GSF volume was Â± 46% in the first observation and Â± 32% in the fourth observation. It was concluded that the use of a fixed orthodontic appliance sharply increase plaque accumulation on the 14th day. Increase of GSF volume is relatively small on day 14 and day 28, but on day 42 the increase becomes sharp. The increase of GI is constant from every time. There is a correlation between plaque accumulation with GSF volume before and after treatment.